Determination of steroid hormones in bovine milk by LC-MS/MS and their levels in Swiss Holstein cow milk. Issue 5 (3rd May 2016) - Goyon, Alexandre; Cai, Julia Zhenzhen; Kraehenbuehl, Karin; Hartmann, Christoph; Shao, Bing; Mottier, Pascal
ABSTRACT: Synthetic and natural steroid hormones have attracted some attention in recent years as endocrine active substances (EAS) that interact or interfere with the endocrine system. Endogenous hormones occur naturally in food of animal origin, among which bovine milk represents an important source. This study was conducted to determine the occurrence of steroid hormones (oestrogens, androgens, progestogens and glucocorticoids) in cow's milk samples from three farms in Switzerland. An isotope dilution liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the quantification of 12 hormones in milk. Some hormonal levels from individual cows showed large variations. The average levels of the hormones analysed (17α-estradiol = 31 ng kg – 1, 17β-estradiol = 6 ng kg – 1, estrone = 159 ng kg – 1, 4-androstenedione = 684 ng kg – 1, progesterone = 15486 ng kg – 1, 17-hydroxyprogesterone = 214 ng kg – 1, cortisone = 112 ng kg – 1, and cortisol = 235 ng kg – 1 ) were comparable with literature data. Estriol, testosterone and androstenediols were not detected at their respective limit of quantification. No significant differences of hormonal content among milk from cows at different lactation/calving numbers were evidenced, except for progesterone and 4-androstenedione. Due to confounding parameters linked to the physiological stage of the animal, like pregnancy and gestational stage (pregnancy trimester), the causal correlation between the variation of the levels for these two hormones and the lactation/calving number could not be unambiguously demonstrated.